2014
DOI: 10.4238/2014.april.8.14
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract postconditioning reduces myocardial ischemia reperfusion injury

et al.

Abstract: ABSTRACT. We examined the protective effects of Ginkgo biloba extract (EGb761) postconditioning on myocardial ischemia reperfusion injury in rabbits. Four groups of 8 white rabbits were allocated to: pseudo surgery group: the left coronary was lined without blocking for 160 min after thoracotomy; ischemia and reperfusion group (IR): the left anterior descending coronary artery was blocked for 40 min and reperfused for 120 min; ischemic postconditioning group: the left anterior descending artery was ligated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
(11 reference statements)
2
15
0
Order By: Relevance
“…Modern medicinal uses for Ginkgo are solely derived from leaf extracts, the main components of which are flavones and terpene lactones. Ginkgo biloba extract has been demonstrated to have anti‐inflammatory, antioxidant and antiarrhythmic activities and has been widely used in the prevention and therapy of cardiovascular diseases . The present study investigated the therapeutic effects of Ginkgo biloba extract on VMC and explored the potential mechanisms.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Modern medicinal uses for Ginkgo are solely derived from leaf extracts, the main components of which are flavones and terpene lactones. Ginkgo biloba extract has been demonstrated to have anti‐inflammatory, antioxidant and antiarrhythmic activities and has been widely used in the prevention and therapy of cardiovascular diseases . The present study investigated the therapeutic effects of Ginkgo biloba extract on VMC and explored the potential mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“…Ginkgo biloba has existed on earth for 250 million years, and is called “living fossil.” Utilizing Ginkgo biloba leaves as an herbal medicine for the treatment of various diseases can be traced back to thousands of years in China . Ginkgo biloba extract has been demonstrated to protect against cardiac ischemia‐reperfusion injury, and have antiarrhythmic effects on cardiac reperfusion‐induced arrhythmias . A recent study has reported that Ginkgo biloba extract could inhibit rat myocardial remodeling after acute myocardial infarction via decreasing the expression of type I collagen, MMP‐2, and MMP‐9 proteins in myocardial cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanisms of neuroprotective effects of EGb761 are of multiple-aspects, including anti-apoptosis, anti-inflammatory, protecting mitochondria24, etc. Accumulating evidences also demonstrate that EGb761 possesses good protective effect on cardiovascular diseases252627. Recent study showed that EGb761 exerts its anti-inflammatory effect by inhibiting several pro-inflammatory mediators and signaling pathways28.…”
mentioning
confidence: 99%
“…The effective components of ginkgo-diyidamolum include extracts of traditional Chinese medicine, folium ginkgo, and western medicine, dipyridamole. The former one can be specifically against the platelet activating factor [15][16][17], while the latter one can inhibit adenosine diphosphate and thromboxane [18]. TRAIL is also included in tumor necrosis factor receptor which can induce apoptosis through two cascade amplifier channels, nuclear factor-kappa B and caspase [22][23][24].…”
Section: Discussionmentioning
confidence: 99%